2021
DOI: 10.3390/ijms22052438
|View full text |Cite
|
Sign up to set email alerts
|

Keratinocytes Migration Promotion, Proliferation Induction, and Free Radical Injury Prevention by 3-Hydroxytirosol

Abstract: 3-hydroxytyrosol (HT) is the main phenolic compound found in olive oil with known antioxidant, anti-inflammatory, and antimicrobial properties in several dermatological conditions, both when taken in the form of olive oil or pure in cosmeceutical formulations. To date, its direct effect on the wound healing process and the molecular mechanisms involved have not yet been elucidated. Thus, in the present study, we aimed to explore its effects in vitro in epidermal keratinocyte cultures focusing on the molecular … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 68 publications
1
10
0
Order By: Relevance
“…Similarly, the protective role of viability was observed in those cells pre-treated with Htyr to which H 2 O 2 was subsequently added, significantly reducing cell apoptosis and showing antioxidant activity. 121…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, the protective role of viability was observed in those cells pre-treated with Htyr to which H 2 O 2 was subsequently added, significantly reducing cell apoptosis and showing antioxidant activity. 121…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, it could improve the cell migration through the activation of some tissue remodeling factors. 121 Uvaol (natural pentacyclic triterpene found in olives and virgin olive oil)…”
Section: -Hydroxytyrosolmentioning
confidence: 99%
“…In in vitro studies, HTyr was found to inhibit the production of nitric oxide and PGE-2 and the expression of cyclooxygenase-2 (COX-2) and metalloproteinase-9 and to increase the production of TNF-α in monocytes [ 66 ]. HTyr treatment has promoted the proliferation and migration of human keratinocytes, porcine vascular endothelial cells, and HUVEC-C cells, thereby favoring angiogenesis and the re-epithelialization of skin wounds [ 67 , 68 , 69 ]. The antioxidant activity of HTyr was demonstrated in human keratinocytes subjected to UVB rays, observing that it protects against DNA damage and reduces intracellular ROS [ 70 ].…”
Section: Resultsmentioning
confidence: 99%
“…At the end of the treatment with H 2 O 2 , methanol extract of Garcinia mangostana arils (1 µg/mL) and mangostanin (10 µM), cells were washed with ice-cold PBS 2% FBS and loaded with 20 µM of H 2 DCFDA for 30 min. The cells were washed again with PBS 2% FBS, acquired by flow cytometry where at least 10,000 events were collected and next analyzed by Cell-Quest Pro software (BD Biosciences, San Jose, CA, USA) [58].…”
Section: Determination Of Reactive Oxygen Species (Ros)-flow Cytometr...mentioning
confidence: 99%